Competitiveness of Vietnamese External Audit Firms : Reality, Strategies for Improving in Global Integration Conditions - Hai, Phan Thanh (International Journal of Publication and Social Studies, 2017)
Until now, The Vietnamese auditing industry has been more than 25 years formation and development, contributing directly and indirectly to the development of our country. Throughout the process, improving the competitiveness of the auditing firms is always a concern of the managers in the enterprises and the State management level. This article generalizes the basic views on the competitiveness of auditing firms and provides an analysis of the current state of competitiveness of auditing firms in Vietnam. Specific targets in the recent period (2010-2015). On that basis, we strongly recommend some solution and recommendations to futher improve the competitiveness of Vietnamese auditing firms, especially in terms of joining ASEAN Economic Community (AEC), Trans-Pacific Partnership Agreement (TPP), Free Trade Agreement (FTA).